(untitled) (Research, Society and Development, 2022)
Through the adsorption process studied in this work, the removal of dyes often found in textile industry effluents is sought, through the adsorption of an adsorbent material obtained from the peel of the fruit of Paineira (Chorisia speciosa A. St.–Hil), a species found in abundance in Mato Grosso do Sul, Brazil. The Paineira fruit capsule was subjected to tests to verify its efficiency in the process of removing the CIBACRON® Blue FN-R dye, one of the reactive dyes commonly used in the dyeing of cellulosic fibers. In this process, the influence of the variables: degree of agitation and temperature on the degree of removal of the dye contained in a residual bath was studied. The results showed that the material obtained by grinding the peel of the Paineira fruit in natura has a high adsorption capacity. It was found in the study that the degree of agitation has a significant influence on the degree of dye removal from the residual bath, since the temperature at the levels studied did not have a marked influence on the degree of dye removal. The best results in terms of dye removal from the residual bath were obtained at a temperature of 25°C and at a degree of agitation of 200 rpm. It is concluded that the material obtained from the Paineira fiber capsule is efficient in removing the CIBACRON® Blue FN-R dye.